The development and evaluation of an e-module for pneumatics technology - Lim, Johnson Soon Chong; Md Yunos, Jailani; Spahat, Ghazally (Universiti Sains Malaysia, 2005)
Pneumatics technology is an integral part of industrial automation. The aim of this study was to produce an electronic module (e-module) prototype with a multimedia approach in an attempt to assist students’ understanding of lesson contents. The results of the study revealed that the emodule produced conforms to the requirements by students in terms of contents, teaching strategies, the teaching presentation and software application. The e-module is also found to be suitable to serve as an alternative learning material that assists the learning of pneumatics in the subject of industrial automation.